2000
DOI: 10.1159/000021536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Speaking Rate Manipulations on Acoustic and Perceptual Aspects of the Dysarthria in Amyotrophic Lateral Sclerosis

Abstract: The current study explored the acoustic and perceptual effects of speaking rate adjustments in persons with amyotrophic lateral sclerosis (ALS) and in neurologically normal individuals. Sentence utterances were obtained from the participants at two self-selected speaking rates: habitual and fast. Total utterance durations, segment durations, and vowel formant frequencies comprised the acoustic measures, whereas magnitude estimates of speech intelligibility and severity of speech involvement were the perceptual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
2
3

Year Published

2000
2000
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 31 publications
2
65
2
3
Order By: Relevance
“…Measures of VSA were included as an index of vowel segmental integrity (Turner et al, 1995;Weismer, Laures, Jeng, Kent, & Kent, 2000). Previous research has suggested that changes in clear speech differentially affect tense and lax VSA (Chen, 1980;Lam et al, 2012;Picheny et al, 1985).…”
Section: Segmental Vowel Measuresmentioning
confidence: 99%
“…Measures of VSA were included as an index of vowel segmental integrity (Turner et al, 1995;Weismer, Laures, Jeng, Kent, & Kent, 2000). Previous research has suggested that changes in clear speech differentially affect tense and lax VSA (Chen, 1980;Lam et al, 2012;Picheny et al, 1985).…”
Section: Segmental Vowel Measuresmentioning
confidence: 99%
“…2 VSA estimates, based on either three (VSA3) or four vowel-systems (VSA4), have formed the basis of many studies investigating the reduction of articulation in patient groups due to a specific condition, or the restoration of articulatory range as a result of treatment. [2][3][4][5][6][7][8][9][10] The results have, however, been variable in terms of articulatory change shown by the VSA metric, with reductions in VSA at times failing to reach significance in cases where a consistent trend of articulatory reduction is observed [11][12][13] (see Sapir et al 9 for a review). In an attempt to address the observed lack of power in the VSA measure, a reorganization of the formant frequency values has been proposed to form a quotient of formant frequency sums into a formant centralization ratio (FCR), so that "the formant frequencies in the numerator are likely to increase, and the formant frequencies in the denominator are likely to decrease with vowel centralization."…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the distances of a specific set of vowel productions within a space enclosed by four corner vowels would likely differ substantially from distances computed for the same vowel productions, but positioned within a system enclosed by three corner vowels. In light of the varying number of corner vowels used in previous studies of speakers with reduced articulatory range, [2][3][4][5][6][7][8]10,14 this instability in the placement of the center point offers a significant reduction in reliability of the metric. This lack of reliability will affect the study of significant articulatory impairment, as well as severely reduce comparability across studies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have noted vowel centralization and reduced vowel space as the common characteristics of vowels in dysarthric speech [1][2][3][4][5][6][7][8][9] . However, the strength of the relationship between intelligibility and the vowel space area varied widely across studies, ranging from 0 to 71%.…”
Section: Introductionmentioning
confidence: 99%